Coping and its association with psychological adjustment: Differences between first‐, second‐, and third‐plus generation adolescents. Issue 3 (21st March 2022) - Tardif‐Grenier, Kristel; Olivier, Elizabeth; Marks, Amy K.; Archambault, Isabelle; Dupéré, Véronique; Gervais, Christine; Hébert, Corinne
Abstract: Introduction: Adolescents with an immigrant background, whether first‐generation (born abroad) or second‐generation (at least one parent born abroad), face challenges that could compromise their psychological adjustment compared to their third‐plus generation peers. Yet, many are developing positively despite the presence of adversity. To understand what contributes to these adolescents' resilience, it can be useful to study the coping strategies they use. Methods: A total of 1036 Canadian secondary school students participated in this quantitative cross‐sectional study ( M age = 12.9; 56% females; 26% first‐generation; 34% second generation; 39% third‐plus generation). Coping strategies (coping orientation to problems experienced inventory) were assessed and their differentiated associations with self‐esteem, anxiety (Screen for Child Anxiety Related Emotional Disorders), and depressive symptoms (Center for Epidemiologic Studies Depression Scale) were analyzed through path analysis and invariance testing. Results: First‐generation adolescents reported more acceptance/reinterpretation and substance use than second‐ and third‐plus generation adolescents. First‐ and second‐generation adolescents reported using religion more than third‐plus generation adolescents. First‐generation adolescents used self‐distraction more often than second‐generation adolescents, who used it more often than third‐plus generation. The use of humor was more prevalent in second‐generation adolescents compared with their third‐plus generation peers. In addition, some associations between coping strategies and psychological adjustment differed across generations. In first‐generation adolescents, behavioral disengagement was significantly associated with fewer anxiety symptoms. The same trend was observed in second‐generation adolescents who used self‐distraction. These avoidant strategies are generally associated with poor psychological adjustment. Conclusions: This study adds new knowledge about differences across generations in the coping strategies used by adolescents to deal with stress. Further practical implications are discussed.